2010
DOI: 10.1002/art.27699
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of intestinal CD4+CD25high Treg cells in patients with ankylosing spondylitis: A putative role for interleukin‐10 in preventing intestinal Th17 response

Abstract: Objective. Subclinical gut inflammation has been demonstrated in patients with ankylosing spondylitis (AS).Intestinal inflammation is a shared feature of ankylosing spondylitis (AS) and Crohn's disease (CD). Shared immunologic and genetic similarities, in both clinical and preclinical stages, and the observation that 7% of patients with AS and initial chronic gut inflammation develop overt CD strongly support the hypothesis that AS patients with more pronounced gut inflammation could be considered to have prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 72 publications
1
34
1
3
Order By: Relevance
“…The increased percentages of the Tregs population in our AS patients suggest that an enhanced immuno-regulatory mechanism is present in disease processing. This may result from the existence of a positive feedback system in which the inducible regulatory T cells are generated and triggered due to ongoing inflammation [27,30,31]. It has been shown that the FoxP3 expression can be induced in human CD4 + CD25 − T cells after cell activation [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased percentages of the Tregs population in our AS patients suggest that an enhanced immuno-regulatory mechanism is present in disease processing. This may result from the existence of a positive feedback system in which the inducible regulatory T cells are generated and triggered due to ongoing inflammation [27,30,31]. It has been shown that the FoxP3 expression can be induced in human CD4 + CD25 − T cells after cell activation [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…With higher TNF-␣ concentration, the function of Tregs to inhibit Teff population could be abolished in autoimmune diseases [17,30,36,37]. Tumor necrosis factor receptor 2 (TNFR2) preferentially express on Tregs and provide Tregs with greater capability to use TNF for cellular activation and expansion, therefore, this pro-inflammatory cytokine-TNF could up-regulate Tregs [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is an activator of T cells, monocytes, and neutrophils, which drives the clearance of pathogens, while IL-10 acts to hinder this process (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Th9 cells also increase in the peripheral blood and synovial tissues in PsA and express a4b7þ, indicating the intestinal origin of these cells [27]. Conversely, in patients with AS, IL-23 over-expression dominates and is mainly detected in the presence of PC without a clearly defined Th17, Th1, and/or Th9 polarization and Treg expansion [33,34].…”
Section: Immune Alterations In the Gut Of Spa Patientsmentioning
confidence: 99%